Irrigation Of Wounds with Red betel 20% And 40% to Bacterial Numbers In Diabetic Foot Infection (DFI) Patients - Sukmana, Mayusef; Nopriyanto, Dwi; Alhawaris (Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: The most frequent complications of diabetes mellitus are Diabetic Foot Ulcers (DFU), which has a risk of death 2.5 times compared to those without DFU. More than half of them have problems with infection (Diabetic Foot Infections). Research on wound washing to control diabetic wound infections originating from phytopharmaca using tropical natural resources such as red betel has not developed. They are a tropical plant that has many benefits containing flavonoids, tannins, alkaloids, saponins. Washing the wound with irrigation and swab techniques using red betel 20% effectively reduces the total number of bacteria with diabetic ulcer isolates in white mice alloxan-induced. It reduces staphylococcus growth aureus at concentrations of 10%, 20%, 40%, 80%, 100%. Purpose: This study aimed to determine the effectiveness of wound irrigation red betel 20% and 40% of the bacterial rate in DFI patients.Methods: This study used a quasi-experiment with pre-post test control group design two treatment groups where bacterial samples were taken before and after irrigation using 20% and 40% red betel extracts while the control group used 0.9% NaCl. Sampling using consecutive sampling with a large sample of 10 respondents, the total sample swab is 20 samples. The Levine technique swab does perform in the area of the diabetic wound. Wilcoxon test was used as a different test in each group showing a group.Results: The results showed that the Wilcoxon test was used as a different test in each group showing a group. of 20% p-value 0,109, group 40% p-value 0,109 and a dick group p-value 0,180. Conclusion: There was a decrease in the number of bacteria after irrigation betel leaf extract in all groups. The 40% betel extract irrigation group showed an average reduction in bacterial numbers. The DFI wound had an average difference in all groups but was not significant. The suggestion for research follows: Taking more samples, the use of red betel extract as an alternative for infection control in wounds. Further research can be done by isolating the red betel content need for more sampling